Intervention of Dark Chocolate Consumption on Complaints of Menstrual Pain in Adolescent Girls: Descriptive Case Study - Retnowati, Yuni; Alvionita, Vinny; Lestari, Tanti Tri (Ahmar Metastasis Health Journal, 2025)
The incidence of dysmenorrhoea in North Kalimantan Province is reported at 72.89% for primary dysmenorrhoea and 27.11% for secondary dysmenorrhoea. The aim of this study was to determine the effectiveness of dark chocolate consumption in reducing pain levels among adolescents with dysmenorrhoea. This research employed a descriptive case study method with a midwifery care approach, evaluating two groups: the case group, consisting of adolescent girls with dysmenorrhoea who received an intervention in the form of dark chocolate therapy for menstrual pain complaints, and a control group of adolescent girls with dysmenorrhoea who received no such intervention. The research subjects were two 19-year-old adolescent girls experiencing primary dysmenorrhoea, selected using purposive sampling from midwifery students at the University of Borneo Tarakan. The midwifery care process, including assessment, intervention, and evaluation, was conducted from 1st to 3rd August 2022. The results showed that the adolescent with dysmenorrhoea who received dark chocolate therapy experienced a reduction in pain intensity to a level 2 (mild pain). In contrast, the control subject who only received counselling, without any intervention, reported a reduction in pain to level 5 (moderate pain). It can be concluded that the adolescent with dark chocolate intervention showed a significant decrease in pain level from 7 (severe pain) to 2 (mild pain), while the control subject without intervention showed a less significant decrease from level 7 to level 5. It is recommended that this form of complementary therapy be considered for integration into midwifery care practices as part of a holistic approach to menstrual pain management.